The Indonesian Government’s Diplomacy in Fulfiling the Education Rights of the Children of Indonesian Migrant Workers in Tawau Sabah Malaysia - Rifka Noor Annisa; Moh Nizar (Journal of Paradiplomacy and City Networks, 2022)
This research examined the Indonesian government’s diplomatic attempts to fulfill the right to education in Tawau Sabah, Malaysia. The discussion centered on the steps taken by the Ministry of Foreign Affairs, the Consulate General of the Republic of Indonesia (KJRI) in Malaysia, the Consulate of the Republic of Indonesia (KRI) in Tawau, the Directorate General of Primary and Secondary Education in Indonesia, and the Indonesian Embassy in Malaysia collaborated with the Malaysian Ministry of Education (KPM) in establishing a Community Learning Center (CLC) in Tawau as a venue for the education of the children of Indonesian Migrant Workers. Using a qualitative method, the study discovered that the Indonesian Government has been responsible for ensuring that the educational rights of the Indonesian migrant workers’ children in Tawau Sabah, Malaysia, are fulfilled. Obviously, the Government of Indonesia has collaborated with the Government of Malaysia in this endeavor. In addition to building CLC, the of Indonesian Government attempts to fulfill the educational rights of children migrant workers in Tawau included sending teachers and enabling them to complete their education in Indonesia.